Organizational Influence on the Work Engagement of Instructors in Private Higher Educational Institutions - Hermilina A. Mendoza; Jane A. Manarpiis; Jocelyn L. Reyes (AIBPM Publisher, 2025)
Organizational factors play an important role in molding work engagement and overall employee performance. This study examines the influence of organizational factors on the work engagement of instructors in private higher education institutions in Cavite, Philippines. Using a quantitative research design, data were collected from 150 instructors via an online survey and analyzed using multiple regression analysis. Results show that interpersonal relationships significantly influence all three dimensions of engagement—physical ß = 0.201, p 0.01), emotional (ß = 0.193, p 0.03), and cognitive (ß = 0.165, p 0.05). Work interaction significantly affects physical (ß = 0.233, p 0.004) and cognitive engagement (ß = 0.178, p 0.03), while task characteristics negatively influence cognitive engagement (ß = -0.229, p 0.01). Organizational norms were found to influence only cognitive engagement (ß = 0.176, p 0.02). The findings highlight that interpersonal relationships are the most consistent predictor of holistic engagement. The study recommends that institutions foster strong interpersonal dynamics to enhance motivation, resilience, and instructional performance. These insights provide actionable guidance for institutional leaders and policymakers seeking to strengthen faculty engagement and improve teaching quality in higher education.